2009
DOI: 10.1016/j.jvs.2008.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-bonded ePTFE grafts compared with vein grafts in femoropopliteal and femorocrural bypasses: 1- and 2-year results

Abstract: In this large retrospective study, heparin-bonded ePTFE grafts had 1- and 2-year primary patency results that were not significantly different from those for ASV grafts. Results in BK FP and FC applications were especially promising. Randomized studies comparing the use of heparin-bonded ePTFE and ASV grafts in the treatment of peripheral arterial disease are needed to substantiate our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 18 publications
3
56
1
4
Order By: Relevance
“…11,12 Researchers have proposed the immobilization of the heparin on the graft with covalent end point linkages to maintain a prolonged bioactivity on the antithrombin sites of the bound heparin, 13 and several studies reported promising results with this graft. [14][15][16] We reported satisfactory results also in our multicenter registry 5 at an intermediate follow-up period, with a primary patency rate of 61% and a limb salvage of 83% after 3 years in patients with CLI undergoing below-knee revascularizations. In this study, diabetics accounted for more than 40% of the patients and no influence of diabetes on early and follow-up results was found.…”
Section: Discussionmentioning
confidence: 62%
“…11,12 Researchers have proposed the immobilization of the heparin on the graft with covalent end point linkages to maintain a prolonged bioactivity on the antithrombin sites of the bound heparin, 13 and several studies reported promising results with this graft. [14][15][16] We reported satisfactory results also in our multicenter registry 5 at an intermediate follow-up period, with a primary patency rate of 61% and a limb salvage of 83% after 3 years in patients with CLI undergoing below-knee revascularizations. In this study, diabetics accounted for more than 40% of the patients and no influence of diabetes on early and follow-up results was found.…”
Section: Discussionmentioning
confidence: 62%
“…Our prosthetic graft patency rates for below-knee popliteal bypass are more in alignment with other existing reports. 18,19 AV conduits are well-established as an efficacious means of lower extremity revascularization to distal arterial targets. 20,21 An older review by Gentile et al 22 evaluated their results of AV vs SSGSV for critical limb ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…49,56 For reconstructions that cross the knee joint, grafts with removable external rings are available to help prevent graft compression and/or kinking. Meticulous construction of the distal anastomosis is crucial to avoiding short-and long-term graft failure.…”
Section: Slovut and Lipsitz Surgical Technique And Peripheral Arteriamentioning
confidence: 99%